Kangaroo care in the neonatal ICU: health benefits and maternal-infant bonding (Research, Society and Development, 2022)
Due to technological development and the use of increasingly sophisticated devices, maternal participation is almost nil, which threatens the reestablishment of the bond and attachment between the mother-child binomial. The objective of this work is to describe the benefits of the kangaroo method in the neonatal ICU for health and maternal-infant bonding. The present work is an integrative literature review, and the searches were carried out on August 2, 2022 in the electronic database of PubMed, VHL and Google Scholar. Original articles published between 2017 and August 2022, in Portuguese, English and Spanish, were considered eligible. Duplicate, incomplete studies and those whose title, abstract and objective did not fit the guiding question of the present study were excluded. Thus, only 19 articles answered the guiding question and were included in the review. The results of the present study indicate that the kangaroo method strengthens maternal-infant bonding and attachment, reduces feelings of maternal anxiety and depression, increases milk production and duration of breastfeeding, prevents hospital infections and, consequently, decreases morbidity and mortality. of the neonate and with low weight, stabilizes the vital signs of the NB, improves the baby's sleep quality, as well as helps in the healthy growth and development of the neonate. It was concluded that the kangaroo method is an alternative technique in the care of newborns hospitalized in NICUs, because, as shown in the literature, there are several benefits for the mother-child triad and family members.